An instrument for measuring the influence of consumers' cultural values on functional food perception. Issue 7 (8th March 2021) - Neupane, Saugat; Chimhundu, Ranga; Chan, K.C.
Abstract : Purpose: The purpose of the article is to develop an instrument for measuring the influence of consumers' cultural values on functional food perception. Design/methodology/approach: The study is quantitative in nature and builds on an earlier qualitative study that employed in-depth interviews, thematic analysis and constant comparative analysis to construct a survey instrument which initially had 53 items. The quantitative study involved an online survey that was conducted using this instrument, which resulted in 365 complete cases that included 173 Anglo-Australian, 102 Chinese and 90 Indian respondents living in Australia. The survey data were subjected to exploratory factor analysis using Principal axis factoring, with Promax rotation. Findings: The research has validated that functional food perception is dependent upon consumers' cultural values. The results of the exploratory factor analysis provided a six-factor instrument with 32 items. Research limitations/implications: Only three ethnic groups were involved in this study and that is not entirely representative of Australia or other countries. The instrument, however, will allow researchers in the field of functional food to extend the research to other diverse communities. Practical implications: The instrument will further enable functional food producers and marketers to develop effective marketing strategies based on their knowledge of the influence of cultural values on functional food perception. Originality/value: The instrument developed from this study, for measuring consumers' functional food perception based on cultural values, is the first of its kind.